La inclusión educativa y su incidencia en la formación de las niñas y niños de 4-5 años con necesidades educativas especiales transitorias en el albergue “Padre Julio Villarroel Ocaña” de la ciudad de Loja, periodo 2012- 2013. Lineamientos alternativos - Jaramillo Lapo, Jadira Enith (2015)
This research work relates to the educational inclusion and its impact on the education of girls and children 4-5 years with temporary special educational needs in the Hostel "Father Julio Ocaña Villarroel" of the city of Loja. Alternative Guidelines 2012- 2013 period. Therefore the following overall objective was established :. Sensitize school teachers and parents about the importance of providing quality education and warmth to identify and respond to the temporary or permanent special educational needs of children 4-5 years, attending the Children's Home " Father Julio Ocaña Villarroel "of the city of Loja.Similarly in the methodology were used; the descriptive scientific method, deductive and inductive.The instruments used were: Survey that was applied to the teaching of the Hostel "Father Julio Villarroel Ocana" to identify whether it is implementing inclusive education in the institution. Guide remark served to determine the level of education of girls and children 4-5 years attending the Hostel was used. The total population consisted of 42 participants. The results, after application of the instruments determined that 100% of the teachers surveyed said that inclusive education a positive impact on the formation of 61% of the children who had temporary special educational needs and that in the course of the school year 2012-2013 have been gradually overcome, as they had the decisive and responsible for their educational support, such reason, it was necessary to develop a seminar-workshop activities that allowed providing training to teachers and parents, on the importance of consider the timely help to those children with special educational needs through educational inclusion transient